CHI '05 Extended Abstracts on Human Factors in Computing Systems 2005
DOI: 10.1145/1056808.1056952
|View full text |Cite
|
Sign up to set email alerts
|

Don't take my folders away!

Abstract: A study explores the way people organize information in support of projects ("teach a course", "plan a wedding", etc.). The folder structures to organize project information -especially electronic documents and other filesfrequently resembled a "divide and conquer" problem decomposition with subfolders corresponding to major components (subprojects) of the project. Folders were clearly more than simply a means to one end: Organizing for later retrieval. Folders were information in their own right -representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…The duration and depth of engagement gives confidence as to the internal validity of the findings, but the number of participants remains relatively small, and though consistent with other similar studies in PIM literature (e.g. Alvarado et al, 2003;Bellotti et al, 2003;González and Mark, 2004;Jones et al, 2005) it cannot give external validity to the findings. The sample was sufficiently large to capture and describe in detail a great diversity of folder use, but this cannot be taken to represent a complete spectrum of possible uses and behaviours.…”
Section: Limitationssupporting
confidence: 79%
See 4 more Smart Citations
“…The duration and depth of engagement gives confidence as to the internal validity of the findings, but the number of participants remains relatively small, and though consistent with other similar studies in PIM literature (e.g. Alvarado et al, 2003;Bellotti et al, 2003;González and Mark, 2004;Jones et al, 2005) it cannot give external validity to the findings. The sample was sufficiently large to capture and describe in detail a great diversity of folder use, but this cannot be taken to represent a complete spectrum of possible uses and behaviours.…”
Section: Limitationssupporting
confidence: 79%
“…Consistent with previous work, the study showed that folders could remind participants of past organizational decisions and of necessary action in the present (Barreau and Nardi, 1995). Study participants created folders that reflected their understanding and intentions for activity, as described by Jones et al (2005Jones et al ( , 2006 and these played a part in planning and managing activity. The study also shows the value that representations of folder structures can bring to information work, and the potential for folders to shape and integrate with tasks and the processes of information work more generally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations